NO2 concentrations in Sweden 2010 - Backström, Hans (SMHI - Swedish Meteorological and Hydrological Institute, 2019)
Nitrogen dioxide (NO2) and particulate matter (PM-10) concentrations in ambient air, in Shape format covering Sweden. Data represent annual mean values for year 2010 with 1 km resolution in cities and 11 km resolution in rural areas. The coordinate system is Sweref99 TM. Data has been produced with the SIMAIR system, which consists of the nested models MATCH Europe, MATCH Sweden and the urban background model BUM. PM-10 concentration represents inhalable particles.

Model data built on official environmental reporting. Improved resolution in cities, built in SIMAIR model data with 1 km grid. Emission data based on official sources for international reporting. Meteorological data from Mesan reanalysis.

Kväveoxid (NO2) och partiklar (PM-10) i luften i Sverige för 2010.

För mer utförlig beskrivning se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ECDS0156
Koncentrationer av kvävdedioxid (NO2) i Sverige 2010
Keywords: NITROGEN OXIDES; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Environment; Miljö